Molecular characterization of Tapah fish (Wallago leerii, Bleeker 1851) from Riau Province based on Cytochrome b gen - Roza Elvyra; Nurasiah Nurasiah; Agung Setia Batubara (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Tapah fish (Wallago leerii) is a fish with high economic value in Riau Province. Molecular research on W. leerii is very important to do. This study aims to determine the molecular characteristics of W. leerii from Riau Province based on the Cytochrome b gene. The universal primer Cytochrome b is used for the Polymerase Chain Reaction (PCR) process. The PCR result is a partial Cytochrome b gene with a length of 373 bp. Multiple alignments were performed on nucleotide sequences of the Cytochrome b gene of W. leerii from river of Tapung and Indragiri Riau with the cytochrome b gene of other fish from Genbank and analyzed using the MEGA program version 6.0. Phylogenetic construction using the Cytochrome b gene can distinguish W. leerii from river of Tapung and Indragiri Riau, with other species.Keywords:AlignmentsMolecularGenBank